Double Culprits in a Patient with ST Elevation Myocardial Infarction: A Challenging But Rewarding Case - Eka Ginanjar; Yulianto Yulianto; Simon Salim; Wawan Setyawan (Interna Publishing, 2018)
Myocardial infarction simultaneously involving two or more culprit lesions is extremely rare and usually has a poor clinical outcomes including mortality. Management of this complicated condition is challenging and limited time. Nevertheless, autopsy studies revealed that thrombotic occlusion of more than one major epicardium coronary artery is not uncommon. A 68-year-old woman presented with sudden onset of limited breath and chest discomfort since two hours prior to admission. She also felt exert dyspnoea since one month ago. She has two risk factors that were uncontrolled that is hypertension (HT) and type 2 diabetes mellitus (DM). On admission, she succumbed into cardiogenic shock and pulmonary oedema. ECG revealed a diminished R wave in V2-V4 with ST elevation in V2-V5 and in aVR. Biphasic T wave was seen in V2-V6. The working diagnosis was anterior STEMI, Killip class IV with thrombolysis in Myocardial Infarction (TIMI) score of 8. While being transferred to catheter lab, she gasped, became desaturation, and was intubated prior to procedure. The patient was given double inotropes which run maximally. By Coronary angiography, there were occlusions at the LAD and LCX. Stent was applied at proximal LAD and LCX. Subsequently, patient's condition improved and post-procedure ECG showed improvement in aVR and precordial leads, and ST elevation was significantly diminished from V5 and aVR, and R wave came back in V2-V4. Previous study found around 50% of STEMI patients had multi-vessels diseases. In this case, ECG suggested LAD region infarction with ST elevation in aVR, commonly associated with left main stenosis (LMS) involvement. Thrombus aspiration in LAD and LCX yielded hemodynamic improvement. V-stenting technique, introduced in 1996, allows delivery and implantation of 2 stents together, and therefore shorten the stent deployment time.